Remarks on recent fixed point theorems for compatible maps - S. L. Singh; V. Chadha; S. N. Mishra (International Journal of Mathematics and Mathematical Sciences)
Following Gerald Jungck's formulation of compatibility of maps, several interesting fixed point theorems for such maps have been obtained, wherein at least one of the maps is continuous. The main purpose of this note is to avoid the continuity condition from some of the main results of Jungck et al.